"A little bit happy": How performance metrics shortchange pedestrian infrastructure funding. (December 2018) - Makarewicz, Carrie; Adkins, Arlie; Frei, Charlotte; Wennink, Audrey
Abstract: After decades of inattention to the issue, cities and regions increasingly recognize the role of pedestrian infrastructure to improve safety, public health, air quality, accessibility, travel choices, and economic development. But extraordinary gaps exist between pedestrian infrastructure needs and what is funded and built. To understand why this gap persists, even as attention to pedestrian issues grows, we conducted 50 interviews about pedestrian funding with transportation professionals from different levels of government in three regions that have prioritized active transportation: Chicago, Illinois; Denver, Colorado; and Portland, Oregon. We analyzed interviews along with each region's transportation plans, fiscally constrained budgets, and other policy and planning documents. Our analysis revealed three systemic barriers at the regional level that perpetuate the underfunding of pedestrian infrastructure: (1) overall transportation funding shortages made worse by the substantial and growing burden of operating and maintaining aging regional mobility systems; (2) performance and evaluation metrics used in funding decisions are biased toward regional mobility rather than accessibility; and (3) the relatively small scale of individual pedestrian projects often keeps them from being considered regionally significant or scoring highly on metrics related to regional impact. In addition to identifying the need for additional funding sources, the regions we studied used other strategies to address these challenges that may offer lessons for other regions. These include: collecting new data and establishing performance measures that better capture the benefits of active travel modes and their unique contributions to broad policy goals; coordinating across a region to bundle pedestrian projects into larger funding packages that can meet regional significance criteria; and creating regional pedestrian plans that demonstrate how smaller pedestrian projects contribute to regional goals.